Expression of matrix metalloproteinases in patients with Wegener's granulomatosis. Issue 12 (16th November 2004) - Bjerkeli, V; Halvorsen, B; Damås, J K; Nordøy, I; Yndestad, A; Aukrust, P; Frøland, S S
Abstract : Background: Enhanced activity of matrix metalloproteinases (MMPs) has been reported to have a pathogenic role in several diseases such as cancer and cardiovascular disorders, and seems also to play a part in certain autoimmune diseases. Objective: To examine whether enhanced MMP activity may also have a role in the pathogenesis of Wegener's granulomatosis (WG). Methods: In a study group of 15 patients with WG and 15 controls, plasma levels and gene expression were measured in freshly isolated peripheral blood mononuclear cells (PBMCs) of several MMPs and their endogenous inhibitors (that is, tissue inhibitors of metalloproteinases (TIMPs)) by enzyme immunoassays and RNase protection assay, respectively. Results: Whereas patients with WG in remission had enhanced gene expression of several MMPs and TIMPs in PBMCs, those with active disease had a selective up regulation of MMP-2 and MMP-8 compared with healthy controls, and a down regulation of TIMP-1 and TIMP-3 compared with other patients with WG. Moreover, plasma levels of TIMP-1 and MMP-8 correlated significantly with C reactive protein levels, further supporting an association between activation of the MMP/TIMP system and disease activity in WG. Finally, these changes in MMP/TIMP expression in WG were accompanied by increased total MMP activity in PBMC supernatants, particularly in those with active disease, suggesting a matrix degrading net effect. Conclusion: These findings suggest that disturbed MMP and TIMP activity has a role in the pathogenesis of WG.